Valorization of waste gypsum board as a green adsorbent for efficient fluoride removal in groundwater and wastewater treatment - Lee, Jae In; Kang, Jin Kyu; Lee, Chang Gu; Park, Seong Jik (Environmental Technology and Innovation, 2023)
The escalating generation of construction waste during building reconstruction and remodeling underscores the significance of recycling for environmental preservation and resource conservation. In this context, we propose the valorization of waste gypsum board (WGB), a common construction waste material, as a value-added environmental purification agent. WGB, composed primarily of CaSO4, displays the potential to react with fluoride to form CaF2, making it a promising adsorbent for fluoride removal. Through density functional theory analysis, we determined that WGB possesses mesoporous characteristics, with pore sizes ranging from 1 to 20 nm. While thermal treatment has been effective in enhancing fluoride adsorption on other adsorbents, our investigations revealed that the crystalline structure (CaSO4) of WGB remained unchanged under thermal treatment, limiting its impact on the fluoride adsorption capacity. Nevertheless, WGB exhibited a remarkably high fluoride adsorption capacity (285.90 mg/g), surpassing those of other reported adsorbents. Furthermore, the WGB demonstrated excellent fluoride removal performance, even at higher solution pH levels. In artificial wastewater, a dose of 3.33 g/L WGB achieved a remarkable removal efficiency (> 95%). The applicability of WGB was validated by successful fluoride removal in real wastewater and groundwater, with 94% of fluoride in groundwater removed using 0.33 g/L of WGB and 97% of the fluoride in the wastewater removed with 1.67 g/L WGB. This study opens a promising pathway, demonstrating the potential of WGB as a green adsorbent for the effective treatment of fluorine-contaminated wastewater and groundwater, transcending its traditional role in waste recycling.
Keywords: Adsorption capacities; Building reconstruction; Construction wastes; Environmental resources; Fluoride adsorptions; Fluoride removal; Gypsum board; Recycle; Valorisation; Waste gypsums; Calcium sulfate; Construction waste; Groundwater; Gypsum board; Recycle; Wastewater